Representasi Gender dalam Kakawin Nītiśāstra - Putu Gede Suarya Natha (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
Kakawin Nītiśāstra is a classic Old Javanese literary work that holds significant cultural value, especially within Balinese society, and is widely studied in academic settings. Previous research has primarily focused on its ethical teachings and character education, highlighting its role as a moral guide for life. However, a closer examination of the text reveals stanzas that portray women in ways that contradict this interpretation, specifically presenting them as unequal to men. This study addresses the gap in existing literature by focusing on gender representation in Kakawin Nītiśāstra. Given its portrayal as a "guide" for life, the research aims to critically assess how gender roles are presented and encourage more thoughtful engagement with its teachings. Using Sara Mills' critical discourse analysis framework and a qualitative descriptive method, the study analyzes content. The findings show that men are represented as active subjects who speak about and evaluate women, while women are positioned as passive objects under male control. The discourse reflects a patriarchal ideology, with readers implicitly constructed as male, reinforcing gender norms.